The Influence of Employer Branding and Corporate Reputation on Intention to Apply in the Tobacco Industry: Social Media as Moderating Variable - Erlisa Luanita Yapriono; Endi Sarwoko; Rismawati Sitepu (UNIVED Press, 2026)
Human resources are critical for business success, making competition for top talent increasingly intense. This study examines the influence of employer branding and corporate reputation on job seekers’ intention to apply in the tobacco industry, using PT Hanjaya Mandala Sampoerna (HMSP) as the research context, and evaluates the moderating role of social media, specifically Instagram. A quantitative approach was used with purposive and snowball sampling, involving 160 job seekers aged 22–30 years in Jakarta and Surabaya. Data were collected through online questionnaires and analyzed using PLS-SEM. Results show that social media is the most influential factor in increasing intention to apply, followed by corporate reputation and employer branding. Active communication on social media strengthens corporate reputation, even in industries with negative stigma such as tobacco, while its interaction with employer branding is not significant. These findings highlight the strategic role of social media and reputation in attracting talent in challenging sectors. The study provides insights for companies to integrate authentic employer branding, reputation management, and digital engagement to optimize recruitment.